A short history of European law: the last two and a half millennia - Herzog, Tamar (Harvard University Press, 2018)
"Tamar Herzog offers a road map to European law across 2,500 years that reveals underlying patterns and unexpected connections. By showing what European law was, where its iterations were found, who made and implemented it, and what the results were, she ties legal norms to their historical circumstances and reveals the law's fragile malleability"--